2006
DOI: 10.1002/ab.20155
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect bully‐victims: differential psychosocial risk factors associated with adolescents involved in bullying and victimization

Abstract: The present study examined psychosocial risk factors that differentiated direct and indirect bully-victims from bullies, victims and uninvolved adolescents. A total of 7,290 (3,756 girls) students (ages 13-18 yr) from a region of Southern Ontario, Canada, completed a number of self-report measures to determine the relation between direct and indirect bullying and victimization and several psychosocial risk factors, including normative beliefs about antisocial acts, angry-externalizing coping, social anxiety, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
175
3
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(208 citation statements)
references
References 66 publications
13
175
3
17
Order By: Relevance
“…A particularly valuable distinction borrowed from the bullying literature (Marini et al, 2006;Marini, Dane, & Kennedy, in press), which focuses on the forms, functions and types of involvement, is illustrated in Figure 2.…”
Section: Aspects Of Bullying That Can Contribute To the Understandingmentioning
confidence: 99%
See 2 more Smart Citations
“…A particularly valuable distinction borrowed from the bullying literature (Marini et al, 2006;Marini, Dane, & Kennedy, in press), which focuses on the forms, functions and types of involvement, is illustrated in Figure 2.…”
Section: Aspects Of Bullying That Can Contribute To the Understandingmentioning
confidence: 99%
“…An example of a possible conceptual bridge between incivility and our research on bullying is in the definition we use, which highlights the repeated and systematic use and abuse of power involved in bullying to obtain instrumental and social goals (Marini, Dane, Bosacki, & YLC-CURA, 2006;.…”
Section: Understanding Of the Links Between Incivility And Bullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their dual involvement, they may be most vulnerable and at highest risk for psychosocial problems because they display the behavioral patterns that are distinctive for bullies and for victims. Indeed, a small number of studies have shown that adolescent bullyvictims display a unique combination of psychosocial risk factors consistent with their bullying and victimization experiences (Austin and Joseph 1996;Haynie et al 2001;Marini et al 2006). However, bully-victims do not necessarily demonstrate poorer adjustment than victims on social features that are related to victimization (Marini et al 2006).…”
Section: The Present Studymentioning
confidence: 99%
“…Indeed, a small number of studies have shown that adolescent bullyvictims display a unique combination of psychosocial risk factors consistent with their bullying and victimization experiences (Austin and Joseph 1996;Haynie et al 2001;Marini et al 2006). However, bully-victims do not necessarily demonstrate poorer adjustment than victims on social features that are related to victimization (Marini et al 2006). It has been found that bully-victims find it less difficult to make friends and tend to have slightly more positive relationships with classmates , although other studies suggest that bully-victims are more socially rejected (Perry et al 1988) and less accepted (Austin and Joseph 1996).…”
Section: The Present Studymentioning
confidence: 99%